Rapid hemodilution induced by desmopressin after erythropoietin administration in humans - Sanchis-Gomar, F.; Martinez-Bello, V.; Derbre, F.; Garcia-Lopez, E.; Garcia-Valles, R.; Brioche, T.; Ferrando, B.; Ibanez-Sania, S.; Pareja-Galeano, E.; Gomez-Cabrera, M. C.; Vina, J. (Journal of Human Sport & Exercise, 2011)
We have shown that treatment with desmopressin has a very effective hemodilution effect in healthy humans. These results led us to suggest the possible role of desmopressin to mask blood doping in sports. Based on our results, the World Anti-Doping Agency included the desmopressin in the 2011 List of Prohibited Substances and Methods. On this occasion, the aim of our study was to test the desmopressin-induced hemodilution after rHuEpo administration in humans. This was an intra-subject, crossover study in which five physically active males acted as their own controls. A basal blood sample was taken on their first visit to the laboratory. The next day, the subjects began the treatment. They received a subcutaneous rHuEpo injection three times/week for a two-week period. On the second visit to the laboratory, seventeen days later, a blood sample was taken. Thereafter, the subjects received an oral dose of 4.3 µg/kg of desmopressin and were instructed to ingest 1.5 liters of mineral water during the following fifteen minutes. Three hours after the water ingestion a second blood sample was obtained. The samples were analyzed for hematocrit (HCT), hemoglobin (Hb), reticulocytes (Ret%) and OFF Hr-Score. We found significantly higher HCT, Hb and Ret% levels after rHuEpo administration. Administration of desmopressin significantly decreased the HCT and Hb values but we did not find significant changes in Ret%. The values of the OFF Hr-Score also decreased after treatment with desmopressin. Desmopressin has a very effective hemodilution effect after rHuEpo administration and significantly modifies the hematological values measured by the anti-doping authorities to detect blood doping. We consider that these results reinforce the conclusions reported in our first study and confirm that desmopressin is a very effective masking agent for blood doping.